THEORETICAL AND PRACTICAL COMPLEXITY OF MODELING METHODS. - Erickson, John; Keng Siau (Communications of the ACM, 2007)
The article discusses the theoretical and practical complexity of modeling methods, focusing on the importance of taking into account typical usage when estimating the complexity of systems development methods. The author examines the use of the UML 1.x programming language, which remains the most used of many object-oriented development efforts. Several aspects of the language, including Use Case, Class, Activity, Statechart, Collaboration, Sequence, Object, Component, and Deployment Diagrams, are analyzed.